The Sociology of Science and the Garfield Effect: Happy Accidents, Unanticipated Developments and Unexploited Potentials - Zuckerman, Harriet (Frontiers in Research Metrics and Analytics, 2018)
The Sociology of Science and the Garfield Effect: Happy Accidents, Unpredictable Developments and Unexploited Potentials